Aging Characteristics Consideration in Adaptive Control Design of Grid-Scale Lithium-ion battery - Parthasarathy, Chethan; Laaksonen, Hannu; Alaperä, Ilari (IEEE, 2022)
Lithium-ion battery energy storage systems (Li-ion BESS) have been extensively used for frequency containment reserves for disturbances (FCR-D) and frequency containment reserves for normal operations (FCR-N) in Finland. Typically, for both these applications, active power-frequency (Pf) -droop curve defines the Li-ion BESS active power dispatch to the power grid. However, Li-ion BESS’s performance is affected due to aging resulting in the reduction of its peak power capability and capacity degradation. These issues needs to be considered when defining Pf -droop controller curves. Therefore, adaptive Pf -droop control methodology should be developed which considers battery aging characteristics. This will ensure Li-ion BESS to function within its safe operating margins. It also provides the possibility to automatically modify Li-ion BESS control settings and flexibility services provision capability based on battery performance and aging. In this paper, detailed analysis will be performed on the cycling of real-life Li-ion BESS which is installed and operated in Finland in order to understand the cycle aging process when they provide services to FCR-N markets. In addition, an enhanced, simple adaptive Pf -droop control curve has been proposed by considering the effect of Li-ion battery aging. Effectiveness and the impact of the proposed adaptive droop control curves will be validated by means of case studies
Keywords: adaptive droop control; battery aging; energy storage systems; Lithium-ion batteries; fi=Sähkötekniikka|en=Electrical Engineering|